Fire fighters - Broekel, Ray. (Chicago : Childrens Press, 1981)
Briefly discusses the work, uniform, and tools of fire fighters and describes a variety of fire trucks.
For grades 1-3.
Includes index.
Booklist.
2.4
K-3
Keywords: Fire fighters -- Juvenile literature; Fire fighters; Fire engines; Fire fighters; Fire engines; Fire engines; Fire fighters